Kuhnian perspectives in science education: a comparative review of proponents and skeptics - Perrmansah, Sigit; Rahman, Abdul; Rusmana, Dede; Indrawati, Cicilia Dyah Sulistyaningrum (Intelektual Pustaka Media Utama, 2025)
Despite the abundance of literature discussing Kuhnian views, it is rare to find studies that comprehensively compare the arguments of Kuhnian supporters and skeptics. This study aims to fill the gap by providing a comparative review and synthesis between the two groups of views using the systematic literature review (SLR) analysis technique. The researcher found 1,413 articles reduced with the standard prism protocol to 32 articles that examined Kuhn's views. Proponents support the existence of Kuhn's scientific paradigm where they not only strengthen and consider the importance of Kuhn's theory, but also expand its application to various fields, showing the flexibility and relevance of the theory in understanding the scientific revolution that occurred in various disciplines. Skeptics criticize Kuhn's views such as the ambiguity of the term